Pelatihan Implementasi Pendidikan Literasi Humanis dalam Pembelajaran di Sekolah Dasar - Dina Mardiana; Sapriline Sapriline; Kuswari Kuswari; Simpun Simpun; Chairul Afif (IKIP PGRI Bojonegoro, 2021)
ABSTRACT The Lecturer Program for Assisting Community Empowerment (PDPPM) is one of the schemes in the community service activity at the Faculty of Teacher Training and Education, the University of Palangka Raya (FKIP UPR). This activity program was carried out by the lecturer team from the faculty to provide training to ten class-teachers at SD Muhammadiyah Pahandut and SDN-5 Panarung Palangkaraya through the implementation of humanist literacy education in the integrated thematic learning at both elementary schools. The purpose of this PDPPM program is to help fulfill the pedagogical and professional competencies of those class-teachers in applying learning in the digital era of the 21st century and in the disruption era through humanist literacy knowledge into learning activities at the elementary school. From the results of the evaluation given at the end of the activity regarding teachers’ performance before being given the training, an average score of 61 was obtained. Then, there was an increase after being given the training, where an average score reached 78.1. Thus, the results of this training activity can improve teachers’ competence in mastering basic concepts and theories about humanist literacy education. Keywords: education, humanist literacy, integrated thematic, primary school ABSTRAK Program Dosen Pendamping Pemberdayaan Masyarakat (PDPPM) merupakan salah satu skim dalam kegiatan pengabdian kepada masyarakat di Fakultas Keguruan dan Ilmu Pendidikan Universitas Palangka Raya (FKIP UPR). Kegiatan PDPPM ini dilaksanakan oleh Tim Dosen dari FKIP UPR guna memberikan pelatihan kepada sepuluh orang Guru Kelas di SD Muhammadiyah Pahandut dan SDN-5 Panarung Kota Palangkaraya tentang implementasi pendidikan literasi humanis dalam pembelajaran tematik terpadu di sekolah dasar. Tujuan kegiatan PDPPM ini untuk membantu memenuhi kompetensi pedagogik dan profesional para Guru Kelas dalam mengaplikasikan pembelajaran era digital abad-21 dan era disrupsi tentang pengetahuan literasi humanis ke dalam kegiatan pembelajaran di sekolah dasar. Dari hasil evaluasi yang diberikan terhadap aktivitas dan kinerja guru sebelum diberikan pelatihan dalam kegiatan PDPPM hanya memperoleh nilai rata-rata 61, dan mengalami peningkatan setelah diberikan pelatihan dalam kegiatan PDPMM, yakni rata-rata 78,1. Dengan demikian, hasil kegiatan PDPPM ini dapat meningkatkan kompetensi guru dalam menguasai konsep dasar dan teori tentang pendidikan literasi humanis. Kata kunci: pendidikan, literasi humanis, tematik terpadu, sekolah dasar